ENHANCING STUDENTS’ VOCABULARY MASTERY AND INDONESIAN LANGUAGE PROFICIENCY THROUGH PJBL - Dian Mustikasari; Rina Purwani (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2026)
This study aims to determine how to improve the accurate understanding of Indonesian vocabulary and language skills through project-based learning. The problem among English Education students at UNU Purwokerto enrolled in the Indonesian language course is that many have a shallow, limited vocabulary, and their Indonesian language skills are still not good or correct. The problem formulation in this research is how to improve vocabulary understanding and develop good, correct Indonesian language skills through project-based learning. This research employs Kemmis & McTaggart’s model of Classroom Action Research through project-based learning methods. The class action research was carried out for two cycles, cycle 1 and cycle 2, with a span of one month in four meetings. The pretest results in cycle 1 are still below the complete limit of 60. In the post-test in cycle 1, there was an increase of 72, which was 15%. Furthermore, in cycle 2, the pre-test decreased with an average score of 70, but after implementing learning by assigning students to group discussions and presentations related to vocabulary and standard language in the article, students experienced an increase in the post-test with an average score of 83, which exceeded the finish line with an increase of 28.75%.